Antara Agama dan Imajinasi: Identitas Simbol Ibadah dalam Perspektif Postkomunikasi, Postspiritualitas, dan Hiperspiritualitas - Muslih Aris Handayani; Mukti Ali (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
The practices of worship involve the relationship between humans and themselves, humans and humans, humans and God, and even the relationship between humans and the environment in which they live. With the power of human imagination, when the relationships are practiced properly according to God's direction, then there comes surrender, obedience, and devotion in worshiping God. Spiritual hyperreality or hyperspirituality has created practices of worship that are based on simulating pure rituals as taught by prophets, even though they are ritual formations far from the prophetsnes. Because of the signs of worship practice are based on simulations or self-imaginations, then what appears is falsehood and lies on the signs of the practice of worship. This paper intends to unmask hyperreality in spiritual activities that have been considered sacred. This paper uses semiotics as its approach, especially those introduced by Bartes, Piliang and Baudrillard. this study found that when the practice of worship has been separated from it’s pure rituals as taught by prophets and formed a simulation, the practice of worship is only a means of imaging, style personality, and reproduction machinery.